A Novel Cerium Metal-Organic Framework Constructed from Tri-ligand: Hydrothermal Synthesis and Crystal Structure - Wang, Chong-Chen; Wang, Peng (Asian Journal of Chemistry, 2011)
The cerium based metal-organic framework, Ce(phen)(DA)(OX)0.5(H2O)·2H2O (1) (DA = diphenic acid, OX = oxalic acid), was obtained by hydrothermal reaction of the mixture of CeCl3·7H2O, diphenic acid (DA) and oxalic acid (OX) and 1,10-phenanthroline (phen) in 1:1:1: molar ratio at 140 ºC for 96 h. The crystal of Ce(phen)(DA)(OX)0.5(H2O)·2H2O crystallizes in triclinic, space group p with with cell parameters a = 8.602(14) Å, b = 12.62(2) Å, c = 13.54(2) Å, V = 1282(3) Å3 and Z =1. X-ray diffraction reveals that in complex 1, Ce1 is a nine-coordinated tricapped trigonal prism made up of two nitrogen from phen ligand, two oxygen atoms from the same carboxylate group attached on a diphenic acid ligand, two oxygen atoms from two carboxylate groups attached on another ligand, two oxygen atoms from an oxalic acid ligand and one oxygen atoms from a water molecule. The centers Ce3+ ions are linked by diphenic acid and oxalic acid ligands into one-dimensional infinite and neutral chains.